IMPLEMENTATION OF LEGAL PROTECTION AGAINST CHILD RAPE VICTIMS IN THE FAMILY ENVIRONMENT (STUDY AT UPTD PPA SIDOARJO DISTRICT - Corona Hedo Puspitasari; Jonaedi Efendi (DE RECHT (Journal of Police and Law Enforcement), 2024)
Sexual violence against children in Indonesia continues to increase every year. Perpetrators of violence come from various backgrounds, including those closest to the victim. Sexual violence can occur in various places, including in homes that should be the safest place for children. This study aims to analyze the implementation of legal protection for child rape victims in the family environment. This research is empirical legal research, namely legal research based on facts in the field or direct observation. This research uses qualitative descriptive methods and uses data collection through observation, interviews and documentation at the Technical Implementation Unit of the Women and Children Protection Area (UPTD PPA) Sidoarjo Regency. Thegovernment has issued implementing regulations for the Child Protection Law through Government Regulation No. 78 of 2021 concerning Special Protection for Children, which includes special protection for child victims of sexual crimes. Special protection for children is carried out in the Regional Technical Implementation Unit referring to established service standards. The results of this study concluded that the government imposed a penalty for perpetrators of child rape in the family environment with an additional penalty of 1/3 (one-third) of the criminal threats that should be received and UPTD PPA Sidoarjo Regency has implemented legal protection in accordance with applicable regulations Starting from mentoring, psychological assistance and others. However, there are still several problems that hinder the implementation of child protection such as low public awareness, insufficient reporting rates, unpreparedness of witnesses, and other factors that can hinder the judicial process.